Meningkatkan Kepedulian Terhadap Sampah pada Anak-Anak Panti Asuhan Anak Gembira Kota Medan - Zihan Amira Shandra; Santa Claudiya Novita Simanjuntak; Christin Debora Purba; Jordan Joel Hiroshi Pinem; Fajar Utama Ritonga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Garbage is still a problem that is often faced by the current population. This Mini Project activity was carried out at the Happy Children's Orphanage in Medan City, Tuntungan. The knowledge of the Panti children about waste and how to sort waste is still minimal. The facilities provided are still lacking, of course it will slow down knowledge of the importance of sorting waste. Therefore it is important to cultivate a sense of concern for environmental cleanliness, sorting and processing waste in order to benefit the Earth. The concrete form of this Mini Project is to provide education to the Orphanage children. The method used in carrying out this Mini Project activity is to use the casework method through the Intervention stage in general which consists of Intake Contract Engagement, Assessment, Planning/Planning, Intervention, Evaluation and Termination. The results of this Mini Project activity are that the Orphanage children understand and care about the importance of keeping the environment clean and how to sort waste properly. Apart from that, the Orphanage children can also learn about the benefits of sorting waste and its benefits to the Earth.